The effectiveness of federal renewable policies in India. (April 2017) - Shrimali, Gireesh; Srinivasan, Sandhya; Goel, Shobhit; Nelson, David
Abstract: The Government of India has set ambitious targets for renewable energy. However, unsubsidized renewable energy is still at least 50% more expensive than fossil fuel power, and requires policy support at federal as well as state levels. In this context, a comparative evaluation of the effectiveness of these policies becomes important. Using financial models, we provide a framework to compare existing federal policies – generation based incentive, viability gap funding, and accelerated depreciation – for wind and solar technologies with a new class of debt-related federal policies. Our main finding is that, debt-related policies offer the most potential for cost-effectiveness in the long-term; they also perform well across other criteria. A particularly attractive policy is reduced-cost, extended-tenor debt which, compared to existing policies, would reduce total subsidies by up to 78%, have 100% viability gap coverage potential, and provide 76% of subsidy recovery.